Troy - Benioff, David; Petersen, Wolfgang (Burbank,CA Warner Home Video(3;s Cairo EHE, 2004)
(3GdfLe GdYGdej HQGO HjJ aj hGMO ef CaVd COhQGg aj gPG Gdajde GdPj jLeY Hjf GdMH hGdNjGfI hGdCfGfjI hGdbhI MjK JHOC GdCMOGK HgQhH edcI ESHQWI eY CejQ WQhGOI ajSJNOe edhc GdjhfGf gPG GdCeQ dZRh WQhGOI GdJj dG JbgQs
Special features: Easter eggs; "In the thick of battle" featurette; "From ruins to reality" featurette; "Troy: an effects odyssey" featurette; photo gallery; theatrical trailer
region 1, widescreen (2.40:1) presentation; Dolby Digital 5.1 surround
1
Keywords: (3CadGe SjfeGFjIs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjG cHGQs -- (3ehGO SeYjI hHUQjIs